Guideline Adherence of Asymptomatic Bacteriuria Could Be Improved among General Practitioners in The Netherlands: A Survey Study - Tessa M. Z. X. K. van Horrik; Bart J. Laan; Tamara N. Platteel; Suzanne E. Geerlings (MDPI AG, 2022)
Asymptomatic bacteriuria (ASB) is a common finding in certain populations. This study assessed general practitioners' (GPs') knowledge about ASB and their current clinical practice regarding urine testing. Methods: An online survey was used for GPs in the Netherlands from October to December 2020. Results: In total, 99 surveys were included in the analyses. All GPs strongly agreed with the statements about their knowledge and self-confidence regarding urine diagnostics and treatment of ASB. The median knowledge score was 4 out of 6 (IQR 2 to 6). Most GPs (64 of 92; 70%) followed the guideline for the choice of urine diagnostics and reported appropriate indications for urine testing. However, 71/94 (75.5%) GPs would treat patients for ASB if they have diabetes mellitus. Further, 34 (37%) of 92 participants would inappropriately repeat a urine test after a patient was treated for a urinary tract infection (UTI). One-third of the GPs responded that ASB was insufficiently addressed within the guidelines for UTI. Conclusion: These results indicate that knowledge about ASB could be improved in primary care in the Netherlands, mainly in diabetic patients that have ASB, as well as for follow-up tests after treatment for UTI.